Przybliżone Metody Obliczania Ruchu Konturu Gaz-Ciecz z Uwzględnieniem Sprężystości Cieczy i Złoża - Filinow, M.W.; Grabarczyk, C. (Engineering Transactions, 1965)
Some simplified methods are proposed for computing the process of oil repulsion by a gas in a porous medium the assumptions being that the liquid is compressible, the gas inviscid and the strata elastic. The repulsion forces is divided into two stages. 1. Until the required pressure is reached at the extraction opening, 2. The stage of liquid extraction at constant pressure as reached at the end of the first stage. Making use of the Barenblat approximate method s e solutions are obtained thus determining the pressure distribution in the liquid region, the displacement of the gas-oil interface and the total time required for the gas to fill the boreholes. Confrontation of the approximate and accurate solution shows admissible discrepancies in filtration problems.